2003
DOI: 10.1128/jcm.41.7.2946-2951.2003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationship between Methicillin-Sensitive and Methicillin-Resistant Staphylococcus aureus Strains from France and from International Sources: Delineation of Genomic Groups

Abstract: Cluster analysis of the SmaI patterns, generated by pulsed-field gel electrophoresis, of 44 methicillinresistant (MRSA) and 118 methicillin-sensitive (MSSA) Staphylococcus aureus strains isolated in various French hospitals and 61 MRSA and 48 MSSA strains from 20 other countries revealed 20 genomic groups distributed into four distantly related phylogenic branches. Eighty-three of the 105 MRSA strains (79%) were clustered in the six genomic groups of phylogenic branch I; and 154 of the 166 MSSA strains (92.8%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0
5

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
3
9
0
5
Order By: Relevance
“…A search in the MLST database (http://www.mlst.net/) revealed that 15 out of the 20 STs identified in the present study are exclusively or mostly associated with MSSA isolates, evidencing a high genetic diversity among the MSSA population, as found by others (2,6). Despite the high diversity, eBURST, a computer algorithm used to solve population structures based on MLST data (8), grouped 67% of the MSSA isolates, including clinical and carriage isolates, into four major clonal complexes (CC30, CC5, CC45, and CC8) corresponding to four of the five major MRSA clusters spread worldwide (7,28,29,34).…”
Section: Discussionsupporting
confidence: 51%
“…A search in the MLST database (http://www.mlst.net/) revealed that 15 out of the 20 STs identified in the present study are exclusively or mostly associated with MSSA isolates, evidencing a high genetic diversity among the MSSA population, as found by others (2,6). Despite the high diversity, eBURST, a computer algorithm used to solve population structures based on MLST data (8), grouped 67% of the MSSA isolates, including clinical and carriage isolates, into four major clonal complexes (CC30, CC5, CC45, and CC8) corresponding to four of the five major MRSA clusters spread worldwide (7,28,29,34).…”
Section: Discussionsupporting
confidence: 51%
“…However, we did not detect the presence of the mercury operon, suggesting that the Nigerian cassette does not carry SCCmercury and that it is a new SCCmec element. Recombination between different SCCmec types and/or local acquisitions may explain the emergence of new resistance elements (5,12,13). Recent data indicated that the local acquisition of SCCmec elements is a frequent phenomenon (24), highlighting the need to compare the molecular epidemiologies of MSSA and MRSA.…”
mentioning
confidence: 99%
“…Multilocus sequence typing (MLST) can also determine the genotypic characteristics of staphylococcal isolates by analyzing ϳ450-bp sequences of seven housekeeping genes (5,10). Previous reports using MLST, pulsed-field gel electrophoresis, spa typing, or SCCmec typing have documented the clonality and evolutionary pathway of S. aureus (3,11,12,29).…”
mentioning
confidence: 99%